CANDIDIASIS IN PERSPECTIVE OF PAKISTAN - Rabeea Rizwan; Zahida Memon; Shehla Shaheen (ziauddin University, 2024)
Candidiasis is one of the common fungal infections. It is known as the disease of people with compromised immunity, that usually infects premature infants, elderly and hospitalized patients with co-morbids. Although a concise national data is unavailable on prevalence of candidiasis in Pakistan but few studies conducted in tertiary set ups have shown prevalence of albicans around 56-59%. WHO has labelled Pakistan having the highest global burden of candidemia (invasive candidiasis) which is exceedingly fatal. Few hospital-based studies displayed vaginitis as frequently occurring candidiasis, ranging from 18 to 38%.While the resistance against commonly used antifungal drugs varies from 34 to 61%. It is noticed that due to environmental variations fungal infections are increasing day by day but at national level no surveillance program has been developed so far. The current review was undertaken to highlight the issues related to incidence, causes, culture and sensitivity pattern of candidiasis in Pakistan and to identify the gaps in this domain. There is intense urge to formulate new drugs or alternative agents with better efficacy, safety and affordability to combat this slowly growing enemy (candida). Therefore, preventive steps should be taken to decrease its spread, especially in hospital settings which are the main harbor of these infections. KEYWORDS: Fungi, Candidiasis, C. albicans, fluconazole